Extracellular transmission of a DNA mycovirus and its use as a natural fungicide - Yu, Xiao (National Academy of Sciences, 2013)
Mycoviruses are thought not to be infectious as free particles and to lack an extracellular phase in their life cycles, limiting the broad use of hypovirulence-associated mycoviruses in controlling fungal disease. Here, we demonstrate that purified particles of a DNA mycovirus, Sclerotinia sclerotiorum hypovirulence-associated DNA virus 1 (SsHADV-1), are infectious when applied extracellularly to its host Sclerotinia sclerotiorum. Virus particles isolated from an infected host can infect the hyphae of virus-free S. sclerotiorum directly when applied to hyphae grown on potato dextrose agar or sprayed on leaves of Arabidopsis thaliana and Brassica napus, regardless of vegetative compatibility affiliation. When applied to leaves, the virus can suppress the development of lesions. SsHADV-1 can also reduce disease severity and enhance rapeseed yield significantly under field conditions. SsHADV-1 has a narrow host range; it can infect Sclerotinia minor and Sclerotinia nivalis, sister species of S. sclerotiorum, and cause debilitation of these two fungi, but cannot infect or transfect other tested fungi, such as Botrytis cinerea, which shares the same family with S. sclerotiorum. Virus particles are likely to be very stable on the leaves of A. thaliana plants because viral DNA could be detected at 15 d postinoculation on unwounded leaves and at 10 d postinoculation on wounded leaves, respectively; however, this virus could not infect and move in plant cells. Our findings may prompt a reconsideration of the generalization that mycoviruses lack an extracellular phase in their life cycles and stimulate the search for other DNA mycoviruses with potential use as natural fungicides.